Synthetic LXR agonist attenuates plaque formation in apoE-/- mice without inducing liver steatosis and hypertriglyceridemias⃞ - Adelheid Kratzer; Marlene Buchebner; Thomas Pfeifer; Tatjana M. Becker; Georg Uray; Makoto Miyazaki; Shinobu Miyazaki-Anzai; Birgit Ebner; Prakash G. Chandak; Rajendra S. Kadam; Emine Calayir; Nora Rathke; et al. (Journal of Lipid Research, 2009)
Liver X receptors (LXRs) are important regulators of cholesterol and lipid metabolism. LXR agonists have been shown to limit the cellular cholesterol content by inducing reverse cholesterol transport, increasing bile acid production, and inhibiting intestinal cholesterol absorption. Most of them, however, also increase lipogenesis via sterol regulatory element-binding protein-1c (SREBP1c) and carbohydrate response element-binding protein activation resulting in hypertriglyceridemia and liver steatosis. We report on the antiatherogenic properties of the steroidal liver X receptor agonist N,N-dimethyl-3β-hydroxy-cholenamide (DMHCA) in apolipoprotein E (apoE)-deficient mice. Long-term administration of DMHCA (11 weeks) significantly reduced lesion formation in male and female apoE-null mice. Notably, DMHCA neither increased hepatic triglyceride (TG) levels in male nor female apoE-deficient mice. ATP binding cassette transporter A1 and G1 and cholesterol 7α-hydroxylase mRNA abundances were increased, whereas SREBP1c mRNA expression was unchanged in liver, and even decreased in macrophages and intestine. Short-term treatment revealed even higher changes on mRNA regulation. Our data provide evidence that DMHCA is a strong candidate as therapeutic agent for the treatment or prevention of atherosclerosis, circumventing the negative side effects of other LXR agonists.